Firm Characteristics and Carbon Emission Transparency: Evidence from Indonesian Energi Companies in 2024 - Ni Wayan Apriyani; A.A. Pt. Agung Mirah Purnama Sari; Anak Agung Istri Pradnyarani Dewi (Golden Ratio of Finance Management, 2026)
The objective of this study is to examine how energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2024 disclose their carbon emissions in relation to profitability, leverage, and firm size. The study's urgency stems from the fact that businesses in the energy sector contribute significantly to greenhouse gas emissions, making carbon emission reporting transparency an essential component of establishing a company's reputation and guaranteeing its sustainability. In addition, Indonesia’s emission reduction targets and implementation, as reported by Climate Action Tracker 2024, are still insufficient to keep global warming below 1.5°C. The sampling method employed is saturated sampling (census) based on specific criteria, resulting in 75 observations. This study uses cross-sectional data for the year 2024. The analytical model applied is ordinary least squares (OLS). OLS is chosen as it is a BLUE estimator and is considered the most appropriate method for testing causal relationships among observed variables. Firm size has a positive impact on carbon emission reporting, but profitability and leverage have no effect, according to empirical findings. The study's conclusions contradict legitimacy theory because carbon emission reporting policies are still optional, which encourages businesses to prioritize improving their financial performance. However, large firms tend to increase the transparency of carbon emission reporting as an effort to maintain reputation and obtain social legitimacy. The results are also not in line with stakeholder theory, as firms with high leverage tend to prioritize financial stability over carbon emission reporting, which requires additional costs.